PARADIGMA KEMISKINAN DALAM PERSPEKTIF ISLAM - Agus, Agusman; Mujiadi (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2024)
Poverty is a condition in which an individual or a group of people, both men and women, are unable to fulfill their basic rights to sustain and develop a dignified life. The dimensions of poverty are interconnected, either directly or indirectly, meaning that progress or setbacks in one aspect can affect progress or setbacks in others. Moreover, poverty primarily affects human beings, both individually and collectively. The causes of poverty vary depending on its type, and there are also numerous indicators of poverty. Efforts to alleviate poverty include providing basic needs such as food, healthcare, and education; expanding employment opportunities; agricultural development; revolving fund provision through credit systems; infrastructure development; as well as guidance and sanitation education. Islam offers solutions to poverty alleviation, including encouraging Muslims to work, redistributing income through zakat, infaq, and sadaqah, among other measures.